What drives the timing of inter-vivos transfers? - Bee Boileau; David Sturrock (Institute for Fiscal Studies (IFS), 2023)
Understanding the drivers of wealth transfers during life is crucial to understanding the intergenerational transmission of inequality, the optimal design of social insurance, and the efficacy of expansionary fiscal policy. To shed light on this, we analyse the relationships between giving and receiving significant wealth transfers and experiencing key life events. We use newly-available data from the UK Wealth and Assets Survey to investigate recipients' self-reported transfer use, alongside measures of life event transitions contemporaneous with transfer receipt. Our findings suggest that substantial intergenerational transfers help recipients to make consumption or investment decisions with a up-front fixed cost, like moving into homeownership, rather than providing intra-family insurance of shocks. This is particularly the case for those with more affluent parents. Events in givers' lives, including receiving an inheritance and being widowed, also have the potential to explain a substantial share of transfers made. Becoming a widow is strongly associated with an increased likelihood of making a transfer, but this is not the case for new widowers, consistent with gender differences in preferences for making transfers.
Keywords: D14; E21; G51; 330; nter-vivos transfers; gifts; loans; wealth